In order to explore the potential for integration of the Internet into ELT in Uzbekistan , it is necessary first to outline the contexts both of ELT and of Internet use.the first section thus presents an overview of Global ELT and examines the nature of - Makhsudova, Oysara (Журнал иностранных языков и лингвистики, 2023)
In order to explore the potential for integration of the Internet into ELT in Uzbekistan , it is necessary first to outline the contexts both of ELT and of Internet use.the first section thus presents an overview of Global ELT and examines the nature of ELT in Uzbekistan .The second section documents current levels of internet use in Uzbekistan it describes various networking projects currently being implemented, and considers current constraints upon the use of the Internet.Finally,it examines the relatively limited integration of the internet into Uzbek ELT to date.